Institutional Profile: University of Chicago Center for Personalized Therapeutics: research, education and implementation science. (September 2013) - Dolan, M Eileen; Maitland, Michael L; O'Donnell, Peter H; Nakamura, Yusuke; Cox, Nancy J; Ratain, Mark J
Pharmacogenomics is aimed at advancing our knowledge of the genetic basis of variable drug response. The Center for Personalized Therapeutics within the University of Chicago comprises basic, translational and clinical research as well as education including undergraduate, graduate, medical students, clinical/postdoctoral fellows and faculty. The Committee on Clinical Pharmacology and Pharmacogenomics is the educational arm of the Center aimed at training clinical and postdoctoral fellows in translational pharmacology and pharmacogenomics. Research runs the gamut from basic discovery and functional studies to pharmacogenomic implementation studies to evaluate physician adoption of genetic medicine. The mission of the Center is to facilitate research, education and implementation of pharmacogenomics to realize the true potential of personalized medicine and improve the lives of patients.